Employing Psychological Warfare Patterns at The level of the State's Comprehensive Strategy) A Vision to Enhance The Capabilities of The Ruling Political System (: international and political journal - Muhammad, Major General Dr. Yasser Abdul Jabbar (The International and Political Journal, 2024)
The term "psychological war" was used metaphorically to express those behavioral activities and events that do not use the armed forces and security services directly, and instead employ emotions, fear, anger, resentful feelings and all the psychological elements responsible for causing mental disorders and psychological imbalance. Psychological warfare does not only target the morale of the fighter on the battlefield, but also the people who stand behind the fighter as well as the perceptions of the decision-makers who manage the war. Based on the above, the elements of strength and weakness lie in the efficiency and effectiveness of the ruling political system, and this is what this research attempts to clarify its most important intellectual and realistic requirements through three topics in addition to the introduction and conclusion.